Synthesis of New Glucose Derivatives Containing Various Moieties of Possible Biological Activity - Nabeel A. A.Al-Redha, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
This paper describes the synthesis of series of arylthioglycopyranose derivatives was carried out Via alewis acid mediated coupling of the fully acetylated monosaccharide with an aromatic thiol have abiological activity by displacement of an anomeric leaving group with athiol accepter to give the thioglycoside directly.